Penerapan Metode Think Pair Share untuk Meningkatkan Hasil Belajar Bahasa Arab Madrasah Tsanawiyah Nurul Jadid - Umar Manshur; Abdulfatah Daniyullah (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2022)
Arabic is a common language learned by Muslims in Indonesia. As an Indonesian, learning Arabic is certainly not as easy as learning your mother tongue. There are four things that students need to have, namely speaking, reading, writing and listening skills. Thus it is necessary to have a method to support students so that it is easier to learn Arabic, one of which is by using the cooperative method of the think pair share learning model. Through this method students can more easily understand Arabic, and can also make the atmosphere in the classroom more conducive. This research was conducted at MTS Nurul Jadid Religious Program with a quantitative approach. PTK is a type of research method used in this study which was held in two cycles. Data collection was carried out using test, observation and interview methods. The results obtained during the learning process took place, namely an increase in student learning outcomes by applying the thin pair share method with a result of 62.5% increasing to 83.33%.